Changes in subcortical grey matter in rheumatoid arthritis - Wartolowska, K; Hough, MG; Wordsworth, P; Tracey, I (2011)
Introduction: Recently it has been demonstrated that chronic pain is associated with structural brain changes. So far there have been no morphometric studies on patients with rheumatoid arthritis (RA). Bekkelund et al. [1], used manual tracing methods, and observed larger brain atrophy in patients with long term RA, than in control subjects. Our previous studies demonstrated that there are no cortical changes in RA. We used FIRST, a shape-based morphometric method to compare shape of subcortical grey matter in RA patients versus healthy controls. Methods: We recruited 31 patients with severe rheumatoid arthritis, treated with non-biological disease-modifying antirheumatic drugs, and 25 age- and sex- matched healthy controls, free of any chronic pain complaint. High-resolution MP-RAGE images were acquired on a 3T Tim Trio scanner (Siemens, Erlangen). Data were analyzed using FIRST, a shape-based morphometry style analysis [2]. We used age and sex as regressors of no interest. In the patient group, only disease duration was entered into the model together with age and sex to investigate whether any of the structural changes were correlated with the duration of disease. Results: We observed a larger right caudate nucleus in the patient group. None of the structures was larger in the control group. There were no correlations between the disease duration and shape changes in any of the subcortical structures in the patient group. Discussion: The observed changes may reflect altered motor feedback related to pain in disability in RA, changes related to activity in the reward system (if we treat pain relief as a reward), finally increase of subcortical grey matter may be associated with alterations in dopaminergic transmission. Conclusions: We suggest that chronic pain in RA is associated with subcortical structural brain changes reflecting neuroplasticity related to chronic pain or motor changes. In the future, a follow-up study in early RA would help to improve our understanding of these changes.